(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Breastfeeding is the first and most important intervention for a child’s survival, good growth, and development.1 Optimal breastfeeding can prevent nearly 12% of deaths, or roughly 823,000 deaths, in children under the age of five each year. This includes starting breastfeeding as soon as possible after birth, providing exclusive breastfeeds for the first six months of life, adding complementary feeds after that time, and continuing breastfeeding until age two.2,3 Only 40% of all Indian newborns are nursed within an hour of birth, and only 50% of children under 6 months are exclusively breastfed, according to the National Family Health Survey (NFHS-4) 2015–2016.4